Genetic variation in threatened conifer Cunninghamia lanceolata var. konishii using ISSR markers: Implications for conservation - Tam, Nguyen Minh; Hoa, Nguyen Thi; Phuong Trang, Nguyen Thi (Academia Journal of Biology, 2012)
We investigated the genetic variation of Cunninghamia lanceolata var. konishii, on basis of eight ISSR markers. Samples from 182 trees of four populations in the Thanh Hoa and Nghe An provinces were included in this study. The ISSR data showed low genetic variability at both population and species level, with an average of 0.1025 and 0.1357, respectively. Genetic differentiation among populations was high (Gst = 0.2554) indicating limited gene flow (Nm = 1.4575). The implication of the results from the study to conserve genetic resources of the species was proposed.